Self-Efficacy As A Moderation Variable In Affect Environment Family And Education Entrepreneurship To Interest Entrepreneurship Student UNY - Nurwetty Miduk Arta Situmorang; Rosidah Rosidah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research aims to find out, ( 1 ) the influence of the family environment in moderating self-efficacy on students' interest in entrepreneurship, and ( 2 ) the influence of education entrepreneurship towards students' entrepreneurial interests with self-efficacy as a moderator.This type of research is causal associative research using a quantitative approach. The population of this study was 1,100 students from the Class of 2021 UNY (FEB, FMIPA, and FISHIPOL). Sampling was based on the Taro Yamane formula of 294 students. The The data collection method used is a questionnaire method which has been tested for validity and reliability with the help of SPSS Statistics 23. The data analysis techniques uses multiple regression analysis and Moderated Regression Analysis (MRA).The research results prove that (1) Self-efficacy weakens the influence of the family environment on entrepreneurship interest of FEB, FISHIPOL, FMIPA Yogyakarta State University students with a regression coefficient value of 0.002 and a sig value of 0.750 > 0.05. (2) Self-efficacy weakens the influence of Entrepreneurship Education on FEB, FISHIPOL, FMIPA students at Yogyakarta State University with a regression coefficient value of 0.012 and a sig value of 0.0.067> 0.005.